Perencanaan Perkerasan Kaku (Rigid Pavement) Menggunakan Metode AASHTO 1993 Pada Ruas Jalan Randublatung-Kedungtuban Kabupaten Blora - Refki Khoirul Safitri; Teguh Yuono; Kukuh Kurniawan Dwi Sungkono (Jurnal Teknik dan Science, 2026)
The Randublatung-Kedungtuban road section in Blora Regency is a Class III road connecting Blora Regency with Bojonegoro Regency and is traversed daily by heavy vehicles, particularly logistics trucks and material transport trucks. The existing flexible pavement condition is considered ineffective in withstanding heavy vehicle loads on expansive soil, resulting in pavement damage such as cracks and potholes that pose a risk of traffic accidents. This design study aims to determine the traffic volume, the subgrade bearing capacity, the rigid pavement structural thickness, and the budget plan (RAB) required for the construction of a rigid pavement on this road section using the AASHTO 1993 method. Data were collected through a 3×24-hour average daily traffic (LHR) survey using CCTV, as well as subgrade bearing capacity testing using a Dynamic Cone Penetrometer (DCP) at 200-meter intervals. The collected data were then processed to determine the concrete slab thickness, reinforcement requirements, joint details, and the budget plan. The design results show a traffic volume of 31,810 vehicles, or 27,637 pcu/day, with a design subgrade CBR value of 6.2%. Based on these results, the planned concrete slab thickness is 25 cm, with transverse reinforcement of Ø13-200 mm and longitudinal reinforcement of Ø10-200 mm, dowels of Ø32-300 mm with a length of 450 mm, and tie-bars of D16-1000 mm with a length of 700 mm. The budget plan required for the construction of the concrete road pavement on this section amounts to Rp.14,290,939,000-,. The results of this design are expected to serve as a reference for the Public Works and Bina Marga Agency of Central Java Province in upgrading the road structure of the Randublatung-Kedungtuban section into a rigid pavement that is stronger, safer, and better suited to traffic demands and local environmental conditions.